Correlation of Cerebrovascular Reserve as Measured by Acetazolamide-challenged SPECT with Angiographic Flow Patterns and Intra- or Extracranial Arterial Stenosis - Ozgur, Hasan T.; Kent Walsh, T.; Masaryk, Anthony; Seeger, Joachim F.; Williams, Walter; Krupinski, Elizabeth; Melgar, Miguel; Labadie, Enrique (American Journal of Neuroradiology, 2001)
BACKGROUND AND PURPOSE: The ability to identify patients at increased risk for stroke from cerebral hemodynamic ischemia may help guide treatment planning. We tested the correlation between regional cerebrovascular reserve (rCVR) on acetazolamide-challenged single-photon emission CT (SPECT) brain scans and intracranial collateral pathways as well as extra- or intracranial (EC-IC) arterial stenosis on cerebral angiography.METHODS: A retrospective analysis of 27 patients who underwent cerebral angiography and acetazolamide-challenged SPECT brain imaging was performed. With cerebral angiography, the anterior, middle, and posterior cerebral artery (ACA, MCA, PCA) territories were evaluated for patterns of flow, including the ipsilateral carotid or basilar arteries, the circle of Willis collaterals, the EC-IC collaterals, and the leptomeningeal collaterals. With acetazolamide-challenged SPECT, the ACA, MCA, and PCA territories were classified as either showing or not showing evidence of decreased rCVR. Statistical significance was determined by the χ2 test.RESULTS: Patients with decreased rCVR had significantly greater dependence on either the EC-IC or leptomeningeal collaterals (42%) than did patients without decreased rCVR (7%). Similarly, the cerebral hemispheres with decreased rCVR showed a higher prevalence of 70% or greater stenosis or occlusion of the ipsilateral EC-IC arteries in the anterior circulation (74%) than did hemispheres with no evidence of decreased rCVR (16%), and this difference was also statistically significant.CONCLUSION: Acetazolamide-challenged SPECT brain scanning provides additional information regarding rCVR that is not reliably provided by cerebral angiography.